?DYES FROM PLANT BIOMASS (Biological Sciences - PJSIR, 1996)
Series of dyes based on sulphur chromophores was manufactured by the baking process involving rice husk from the plant Oryza sativa and wood shavings of the plant Entandrophragma angolense at 230°C1125 mmHg in a pressure vessel for 3 hrs in presence of aqueous sodium sulphide. Following m-toluene extraction and crystallisation, two dyes were obtained, both of which showed remarkable ultra-violet Ivisible absorption maxima at Amax· of 420nm indicating that they both are of one single colour shade. The dyes gave brilliant yellow colouration of average-good fastness ratings to light and alkaline wash on a bleached and mercerised cotton fabric.